Precise Resection and Biological Reconstruction for Patients with Bone Sarcomas in the Proximal Humerus - Li, Jing; Wang, Zhen; Guo, Zheng; Wu, Yaoping; Chen, Guojing; Pei, Guoxian (Journal of Reconstructive Microsurgery, 2012)
Background It is a challenge to perform a joint-preserving resection for patients with bone sarcomas in the proximal humerus. We determined whether osteotomy under navigation guidance made joint-saving resection possible for juxtaarticular humeral sarcomas while adhering to oncological principles. Method Between January 2008 and July 2010, joint-preserving surgeries were performed on six patients with proximal humeral sarcomas under navigation guidance. Five tumors extended to, and one extended beyond, the epiphyseal line. Planned osteotomy under image-guided navigation was employed to achieve a clear surgical margin while preserving the humeral head and rotator cuff. All tumors were removed en bloc and intercalary defects were reconstructed by a combination of allograft and vascularized fibula graft. All specimens were examined for resection margin. Patients were followed up for an average of 19.1 months.Results The entire glenohumeral joint was preserved in five patients and part of the humeral head was saved in one patient. Clear surgical margin was obtained in all specimens. The minimum closest distance between the osteotomy line and tumor edge was 7 mm. No patient experienced local recurrence. One patient developed lung metastasis and was alive with disease. The mean Musculoskeletal Tumor Society (MSTS) 93 score was 92.1%. All reconstruction was in situ at final follow-up. Conclusion With careful patient selection, image navigation-assisted surgery made it possible to excise the bone exactly as seen in orientation in magnetic resonance imaging (MRI) image, yielding a clear margin and preserving all or part of the humeral head in limb salvage procedures for patients with juxtaarticular bone sarcomas in proximal humerus. Level of Evidence Therapeutic study; Level IV.
Keywords: humerus; sarcoma; navigation; joint-preserving surgery; limb salvage